The detrimental effects of power on confidence, advice taking, and accuracy - See, Kelly E.; Morrison, Elizabeth W.; Rothman, Naomi B.; Soll, Jack B. (Organizational behavior and human decision processes, 2011)
► In four studies we find that greater power is associated with less advice taking. ► Confidence in the accuracy of one’s judgment was the mediating mechanism. ► Two other tested mechanisms (affect; perspective taking) did not explain the results. ► The fourth study also showed that higher power participants were less accurate. ► The results were demonstrated using both multi-source field data and experiments. Incorporating input from others can enhance decision quality, yet often people do not effectively utilize advice. We propose that greater power increases the propensity to discount advice, and that a key mechanism explaining this effect is elevated confidence in one’s judgment. We investigate the relationships across four studies: a field survey where working professionals rated their own power and confidence and were rated by coworkers on their level of advice taking; an advice taking task where power and confidence were self-reported; and two advice taking experiments where power was manipulated. Results consistently showed a negative relationship between power and advice taking, and evidence of mediation through confidence. The fourth study also revealed that higher power participants were less accurate in their final judgments. Power can thus exacerbate the tendency for people to overweight their own initial judgment, such that the most powerful decision makers can also be the least accurate.